EXACT SQUARES OF WOR - Sevrasevich, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
A review on collections of poems of Vasyl Moysyshyn. Tiras. – Ivano-Frankivs’k: Lileya-NV, 2000. – 92с; Vasyl Moysyshyn. Beskyd. – Ivano-Frankivs’k: Lileya-NV, 2006. – 94с.